Simultaneous MALI and Ugi polymerization in one‐pot for poly(4‐thiazolidinone‐amide) as AIEgen and Fe3+ ion detection. (9th March 2022) - Zheng, Jinxin; Fu, Congcong; Chen, Zhuo; Zhang, Pengfei; Zhao, Ronghui; Ding, Lan; Liu, Hongmei; Deng, Kuilin
Abstract: In this study, two simultaneous MALI and Ugi polymerizations in one‐pot was performed by combining binary amines, glutaraldehyde, mercaptoacetic acid and t ‐butylisonitrile into one four‐component reaction system. The resulting poly( 4 ‐thiazolidinone‐amide)s (PTZAs) contains both thiazolidinone rings from MALI reaction and amide/thiol groups from Ugi reaction, respectively. Unexpectedly, the strong fluorescence emission at 500 nm of PTZA‐E solution is observed under the excitation of 378 nm, which is attributed to the intramolecular "aggregation" of thiazolidinone rings and amide/thiol groups. And also, PTZAs solution showed an excellent aggregation‐induced emission (AIE) by the clusterization‐triggered emission (CTE) mechanism when adding different amount of precipitant. More interestingly, Fe 3+ ion violently quenched the fluorescence of PTZA‐E via the redox reaction and spectrum overlaps, and the limit of detection (LOD) of PTZA‐E to Fe 3+ ion was measured as 10 −4 mol/L. In brief, the two simultaneous polymerizations in one pot provide a great possibility for the polymer with special structure and performance, also including the direct synthesis of AIE‐active polymers from the accessible non‐AIE monomers.